Decolonizing ethnography and Tribes in India: Toward an alternative methodology - Tripura, Biswaranjan (Frontiers in Political Science, 2023)
This article unravels the many ways of doing ethnography within the area of Tribal studies in India. Historically (methodologically), studies concerning Tribes in India were dominated by colonial ethnographers and explorers. Subsequently, in post-colonial India, such studies became the field of a dominant male caste. From a similar perspective of dominance, these studies on Tribes in India viewed them as either as backward, or from the point of view that ‘civilization’ could be achieved only through bringing them into the mainstream. Scholars who followed such frames of reference failed to reflect on their own dominant social positions in engaging in research projects with their Tribal subjects. Moreover, some of them even stated to have been inspired by the works of Malinowski, whose methodology is considered to be uncritical, non-sensitive and non-reflexive, especially while relating with Tribal studies. The Tribal people in India, therefore, continued to be framed within such a dominant caste perspective, without the slightest effort to treat them as non-caste societies or as equals within caste societies. Methodologically, by positioning myself against such frames of reference while engaging in research within the context of Tribes in India, I draw my research frameworks from those of indigenous methodologies to explore the possibilities of decolonizing ethnography by recognizing many ways of doing. Empirically, I base my engagement with a specific Tribal group (Tripura Tribe) in Tripura, Northeast India. As an Indigenous community within the Indian state of Tripura, Tripura people’s epistemology/worldviews differs from that of the majoritarian Savarna caste society. With an intent to decolonize ethnography from an indigenous context, in this article I demonstrate the many ways of doing ethnography by innovatively engaging with three related methods: the conversational method, engaged observation, and sitting around the fire. This article argues that for any researcher, when engaging in research within the context of Tribes, the methods and frame of reference employed must be congruent with indigenous ways of being, knowing and doing. Further, it also insists that critical reflexivity, responsibility and sensitivity are key to Tribal studies in India.